Saluran Distribusi Pakcoy Pada Puspa Agro Farm Sukabumi - Agis Meisa Shafarah; Ratih Hendraningsih (ECONEUR (Journal of Economics and Entrepreneurship), 2023)
This study aims to determine the distribution channel used by Puspa Agro Farm. The research method used is descriptive method, namely analysis that aims to describe or describe an object of research through data that has been collected and then described and arranged into a format that is easier to understand. Then there were several obstacles that occurred in the distribution so this research was carried out. The conclusion of the research shows that Puspa Agro Farm uses three distribution channels namely, level zero distribution channels, first level distribution channels. Where the distribution channel is applied to help companies optimize market control. The zero-level distribution channel is implemented as an effort by the company to optimize its resources to satisfy customers who come directly to the plantations. The company's second- and second-tier channels reach a wider market to work with retailers, supermarkets and other wholesalers.